2018
DOI: 10.4314/aas.v14i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Academic Dishonesty in Medical Schools

Abstract: Background: Dishonesty can be found in all aspects of human interaction and is known to be rampant in educational institutions. Little is known about it in medical training and the characteristics of those involved. This study explores the factors that drive academic dishonesty among aspiring doctors. Objective: To establish the factors driving academic dishonesty among senior medical students. Design: Cross sectional survey using self-administered questionnaire. Setting: The School of Medicine, Moi University… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
4
0
1
Order By: Relevance
“…For example, on the responsibility indicator, AIS uses the formula "Getting a scholarship is like having a responsibility to serve the nation" and "I feel a good image of campus is a shared responsibility." Meanwhile, with the same indicator (responsibility), PAAIS-24 uses the item formulation "I am responsible for studying the assessment instrument before conducting a peer-assessment," "I am responsible for providing correct information to colleagues who ask questions during group discussions," and others (see items [17][18][19][20].…”
Section: -2-discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, on the responsibility indicator, AIS uses the formula "Getting a scholarship is like having a responsibility to serve the nation" and "I feel a good image of campus is a shared responsibility." Meanwhile, with the same indicator (responsibility), PAAIS-24 uses the item formulation "I am responsible for studying the assessment instrument before conducting a peer-assessment," "I am responsible for providing correct information to colleagues who ask questions during group discussions," and others (see items [17][18][19][20].…”
Section: -2-discussionmentioning
confidence: 99%
“…The percentage is high, and if this condition is not immediately changed with a comprehensive and contextual prevention and evaluation approach, then the problem of academic integrity will reduce the value of originality to advance knowledge and create future generations of scientists with integrity [10] and has the potential to be an indicator of student unprofessional behavior in the future in their work [14]. This justification is substantial because students with academic integrity problems have a 70.4% chance of committing the same fraud in the future [19]. The data above confirms that the problem of academic integrity is not only related to students, but peers have a strategic and crucial role in provoking problems and restoring students' academic integrity at universities.…”
mentioning
confidence: 99%
“…Through meta-analysis, Whitley and Keith-Spiegel (2002) stated that the leading causes of academic dishonesty were performance issues, academic and non-academic external pressures, biased professors, and lack of effort. A study conducted by Musau and Boibanda (2018) revealed that medical students who observed cheating and dishonest acts were more likely to depict dishonest acts in their student and practical life. Therefore, the leading factor of academic dishonesty was witnessing or seeing academic dishonesty in action.…”
Section: Outcomes Of Academic Dishonestymentioning
confidence: 99%
“…They seek help from their colleagues for serving passing grades (Griebeler, 2017). In higher learning institutes such as universities, academic dishonesty is the most problematic and disturbing issue where several moral and ethical values are usually ignored [Akakandelwa, et al (2013); Musau and Boibanda (2018)]. Students and teachers both adapt dishonest ways for getting academic better grades and passing the students for the requirement of degree (Tadesse and Getachew, 2010).…”
Section: Outcomes Of Academic Dishonestymentioning
confidence: 99%
“…Banyak tercatat plagiasi di berbagai lembaga Pendidikan, baik di level sekolah maupun di Perguruan Tinggi. Beberapa penelitian mencatat ketidakjujuran akademik (academic dishonesty) mewabah dan terjadi di mana saja, bukan hanya di Indonesia tetapi juga di negara-negara lian di dunia (Kam, Hue & Cheung 2018;Yussof & Ismail 2018;Musau & Boibanda 2018). Sementara akibat buruk menghantui setiap saat dari plagiasi dan segala bentuk kecurangan ini.…”
Section: A Pendahuluanunclassified